OPTIMASI PENJADWALAN PRODUKSI ROTI TIPE FLOWSHOP DENGAN METODE BRANCH AND BOUND - Adham firmansyah; Adli lesmana, Paduloh (ADISAM PUBLISHER, 2025)
Production scheduling is one of the important aspects in operations management to ensure the efficiency and effectiveness of the production process. This research focuses on bread production scheduling optimization using flowshop type, where the production flow consists of stages that must be followed sequentially. The Branch and Bound method is applied to minimize the total completion time (makespan) by finding the optimal solution from various possible job sequences. The results show that this method is able to produce an optimal production schedule, by reducing idle time on machines and increasing overall productivity. A case study in a bakery industry showed a reduction in makespan time of up to 15% compared to the conventional method. This finding is expected to be a practical solution for small and medium industries (SMIs) in improving production efficiency. In addition, this research contributes to the development of science in the field of operations management, particularly in flowshop type scheduling